The Stock Market and Capital Accumulation - Hall, Robert E (American Economic Review, 2001)
The value of a firm's securities measures the value of the firm's productive assets. If the assets include only capital goods and not a permanent monopoly franchise, the value of the securities measures the value of the capital. Finally, if the price of the capital can be measured or inferred, the quantity of capital is the value divided by the price. A standard model of adjustment costs enables the inference of the price of installed capital. Data from U.S. corporations over the past 50 years imply that corporations have formed large amounts of intangible capital, especially in the past decade. (JEL E44, G12)